Geographical analysis of the temporary space behavior of sound intensity in barrio Escalante, San José, Costa Rica. November 2021 to March 2022 - Guillén Montero, Douglas Alberto (2024)
Noise Pollution is considered one of the biggest health risks in modern society worldwide, partly caused by city dynamics. Although its recognition as a health Hazard is recent and its effects have become considered a health problems, actions, and policies to combat it are not yet common in big cities. This article shows the results of a geographical analysis where this type of pollution was evaluated in Barrio Escalante, the objective was to analyze the spatial-temporal behavior of sound intensity during October 2021 to March 2022. In order to achieve that objective, a quantitative study was developed with  sound level meter measurements. This allowed  measuring the intensity of the sounds in different places of Escalante, in two periods: day and night. Decibels were then classified by cycle according to their intensity on a scale of one to five. This is how the general sound index (GSI) was subsequently obtained and so the sound intensity plane of the study area.